Recurrence hazard rate in patients with hepatocellular carcinoma and bile duct tumor thrombus: a multicenter observational study. Issue 10 (October 2022) - Xiang, Yan-Jun; Sun, Ju-Xian; Wu, Jia-Yi; Wang, Kang; Feng, Jin-Kai; Wei, Yong-Gang; Zhou, Jian-Yin; Zhang, Zhi-Bo; Zhang, Yu-Qing; Qin, Ying-Yi; Yan, Mao-Lin; Cheng, Shu-Qun
Abstract: Background: Patients with hepatocellular carcinoma (HCC) bile duct tumor thrombus (BDTT) have a high rate of postoperative recurrence. We aimed to describe the patterns and kinetics of recurrence in BDTT patients and provide management options accordingly. Methods: This retrospective study included 311 HCC patients with BDTT who underwent surgery from 2009 to 2017 at five centers in China. The hazard rate of recurrence was calculated using the hazard function. Results: The hazard rate of intrahepatic recurrence was higher than that of extrahepatic recurrence (0.0588 vs. 0.0301), and both showed a decreasing trend, and the intrahepatic recurrence and extrahepatic recurrence risk decreased to a lower level after 40 and 20 months, respectively. Patients who underwent anatomic resection had a consistently lower hazard rate of recurrence than patients who underwent nonanatomic resection, whereas patients who received postoperative adjuvant transarterial chemoembolization (TACE) mainly had a lower hazard rate of recurrence in the first year than patients who did not. Conclusion: The follow-up of BDTT patients should be at least 40 months because of its high rate of recurrence, in parallel with the need for vigilance for extrahepatic recurrence within 20 months. Anatomic hepatectomy and adjuvant TACE are recommended to improve BDTT patient outcomes.